The Effect of A Skin-to-Skin Contact Educational Program on Midwives’ and Nurses’ Knowledge of Early Essential Newborn Care - Agus, Yenita (Indonesian Journal of Global Health Research, 2025)
Despite a decline in infant mortality rates (IMR) over the years, it remains a critical issue. Evidence-based interventions could prevent many infant deaths, but barriers such as a lack of health specialists and poor care quality persist. This study aims to assess the impact of an educational program on skin-to-skin contact to promote Early Essential Newborn Care (EENC) among midwives and nurses. Objective to evaluate the effectiveness of an educational program on skin-to-skin contact in improving midwives' and nurses' knowledge and skills related to EENC. A quasi-experimental design without a control group was used. Participants were selected through purposive sampling based on two criteria: 1) Midwives and nurses working in delivery rooms or perinatology units, and 2) Those with over five years of experience. Recruitment involved distributing cooperation requests to midwives and nurses at government hospitals and community health centers across Indonesia. Ultimately, 32 participants were enrolled. The study employed a self-administered questionnaire, pre-test and post-test assessments on skin-to-skin knowledge and skills, and training through video and lecture. Data analysis included descriptive statistics and t-tests. The average age of participants was 41.5 years (SD = 9.57). The training significantly improved knowledge (p = 0.003), though two of twelve questions showed no significant change. Limited participation in EENC training was observed. While the educational program improved overall knowledge, certain areas need further attention. Regular training and continuing education are essential for enhancing midwives' and nurses' skills. Future research will focus on evaluating newborn resuscitation and care initiatives, particularly breastfeeding knowledge.